Novel Asymmetric Y Design of Fascial Sling for Restoration of Oral Competence and Adequate Mouth Opening in Oral Commissure Defects Post-Malignancy Resection - Vimalendu Brajesh; Sukhdeep Singh; Deepak Sarin; Aditya Aggarwal; Sanjay Mahendru; Hardeep Singh; Rakesh Kumar Khazanchi (Indian Journal of Plastic Surgery)
Reconstruction of through-and-through defects of cheek and commissure resulting from cancer resection are challenging. The specialized function of oral competence that the oral commissure and lip play is difficult to replicate with flap only reconstruction. Static slings play an important role in improving the functional and aesthetic outcome. The asymmetric “y” fascial sling helps in achieving the goals of oral competence along with adequate mouth opening. A total of 10 patients were operated by this technique. The results were satisfactory in terms of functional and aesthetic outcome postsurgery and were maintained 6 months postradiation.